Evaluation of Perioperative Complications in the Management of Biliary Atresia - Du, Min; Wang, Junfeng; Tang, Yue; Jiang, Jingying; Chen, Gong; Huang, Yanlei; Shen, Zhen; Dong, Rui; Zheng, Shan (Frontiers in Pediatrics, 2020)
Purpose: To analyze the influence of perioperative complications in the management of biliary atresia (BA). Methods: A retrospective study was performed using a total of 422 BA patients who underwent Kasai portoenterostomy (KPE) in a single institution between February 2016 and May 2017. Data on patients’ clinical characteristics, laboratory examinations, perioperative complications, and outcomes were collected. Unpaired 2-tail t test and chi-square test were employed for the comparison between BA patients with and without perioperative complications. Cox regression analysis was used to screen the risk factors for 2-year NLS in BA, and their influence on the 2-year NLS was analyzed using Kaplan-Meier survival analysis as well as the log-rank test. Results: The incidence of perioperative complications, 6-month jaundice clearance (JC) and 2-year native liver survival (NLS) rate were 60.4%, 59.5% and 56.6%, respectively. Patients with perioperative complications had lower serum albumin (ALB) level, but higher aspartate aminotransferase-to-platelet ratio index (APRI) and international normalized ratio (INR) levels when compared with those without perioperative complications (ALB, P<0.05; APRI, P<0.01; INR, P<0.05). Moreover, perioperative complications were correlated with glucocorticoid administration (P=0.002). Univariate Cox regression analysis showed no relationship between perioperative complications and 2-year NLS (P>0.05). However, multivariate Cox regression analysis indicated 6-month JC was an independent protective factor for 2-year NLS (P<0.0001, HR=0.074, 95% CI: 0.05-0.11), and concordance index of this prediction model including age, weight, APRI, glucocorticoid, and 6-month JC was 0.811. Conclusion: Although perioperative complication is common during and after KPE, it had no influence on the prognosis of BA. However, assessment of the serum levels of total bilirubin after KPE may serve as important predictors for the outcome in BA.